The Coastal Thanksgiving Tradition (Tradisi Sedekah Laut) in Teluk Penyu Beach, Cilacap - Khusnul Khotimah (IBDA` : Jurnal Kajian Islam dan Budaya, 2018)
This study aims to analyze the coastal thanksgiving tradition and the meaning for the fishermen communities in Cilacap, especially around the area of Teluk Penyu Beach in Cilacap. Fishermen communities in the South of Cilacap cannot be separated from the original character of the Javanese community in general that they have a strong belief to the myth. They still show their honor and respect toward the ancestral spirit called as Kanjeng Ratu Kidul. It is represented through the ritual of giving some offerings to the sea. The traditional ceremony is conducted on the first day of the Javanese calendar year in the month of Sura. The ceremonies are provided to the spirits existing in the surroundings. It is expected that the spirits will not bother the family and the natural environment. The ceremony is also intended to establish a safe and secure environment and to build economic growth and prosperity. This ceremony has a deep meaning for the societies. It contains the values, morals and manners symbolized in the ceremonies. The meaning, then, affects the behavior of the fishermen’s life; for example, they are sure that they will be safe from dangers when sailing and they also will feel courageous during the sailing though they only use traditional equipment. The coastal thanksgiving tradition continues to exist although there are some efforts from Islamic organizations to reject the tradition. However, Cilacap societies still devote their trust on the spirits of animism and dynamism that have a close relation to their lives. They also have a very strong bond of solidarity and blood connection to their ancestors. That tradition is also included as a medium of thanksgiving celebration that becomes a part of Javanese characteristic.